2014
DOI: 10.1111/oik.01429
|View full text |Cite
|
Sign up to set email alerts
|

Markov models and network analysis reveal sex‐specific differences in the space‐use of a coastal apex predator

Abstract: Understanding the links between external variables such as habitat and interactions with conspecifi cs and animal space-use is fundamental to developing eff ective management measures. In the marine realm, automated acoustic tracking has become a widely used method for monitoring the movement of free-ranging animals, yet researchers generally lack robust methods for analysing the resulting spatial-usage data.In this study, acoustic tracking data from male and female broadnose sevengill sharks Notorynchus ceped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 66 publications
0
40
1
Order By: Relevance
“…For example, Fox and Bellwood (2014) showed that coral reef fishes had spatial networks with small world properties, such that the concentration of fishing effort at known aggregation sites could increase the risk of extinction of coral reef fish species. The potential effect that a disturbance could exert on the coral reef fish community remains an assumption that cannot be fully evaluated using only network analysis, because the temporal dynamic of movement is then ignored (Stehfest et al, 2015). Ferrari et al (2014) showed the utility of using dynamic network models for studying dynamical processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fox and Bellwood (2014) showed that coral reef fishes had spatial networks with small world properties, such that the concentration of fishing effort at known aggregation sites could increase the risk of extinction of coral reef fish species. The potential effect that a disturbance could exert on the coral reef fish community remains an assumption that cannot be fully evaluated using only network analysis, because the temporal dynamic of movement is then ignored (Stehfest et al, 2015). Ferrari et al (2014) showed the utility of using dynamic network models for studying dynamical processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although graph theory can provide crucial information on animal movements within a patch network, inference on population space use dynamics still requires an understanding of the temporal dimension of movement patterns (Jacoby & Freeman, 2016;Nathan et al, 2008). For example, network analysis alone failed to identify preferred sites for a population of broadnose sevengill shark Notorynchus cepedianus, because it did not account for residency period in the different sites (Stehfest, Patterson, Barnett, & Semmens, 2015). Integration of the temporal dimension of movement into a network requires the use of dynamic models, such as a reaction-advection-diffusion model (Barrat, Barthelemy, & Vespignani, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using a spatial network based on counts of directed movements between receivers as proposed by Jacoby et al (2012), which ignores temporal characteristics of movements such as residency periods, we followed the Empirical derived Markov chain (EDMC) analysis proposed by Stehfest et al (2015) which takes into account this temporal dimension. A Markov chain is a random process that undergoes transitions from one state to another (in our case from receiver to receiver) on a state space.…”
Section: Spatial Network Analysismentioning
confidence: 99%
“…To identify preferred use of locations (i.e. receivers) from the movement network, we calculated the eigenvector centrality of each node which is a measure not only of the centrality of a state, but also of the centrality of the states it is connected to (see Stehfest et al, 2015). It is calculated as the dominant eigenvector of the movement network or adjacency matrix and is equivalent to the weighted proportion of the total number of paths in a network going to or coming from a given node (Newman, 2004).…”
Section: Spatial Network Analysismentioning
confidence: 99%
“…We used telemetry to answer two questions: 1) what is the order of habitat preference and movement rates between habitats for blacktip and grey reef sharks, and 2) what is the degree of intra-specific movement rates of individuals between 'sub-habitats' within habitat types? To determine species level habitat preferences and movement among habitats, we performed spatial empirically derived Markov chain (EDMC) analyses (Stehfest et al 2015). EDMC analysis is a form of spatial network analysis that uses a discrete time, stationary Markov chain approach to model the temporal dimension of movements including residency and transition duration (Stehfest et al 2015).…”
Section: Movements and Habitat Usementioning
confidence: 99%